2005
DOI: 10.1161/01.str.0000165929.78756.ed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of C-Reactive Protein Measurement for Assessing the Risk and Prognosis in Ischemic Stroke

Abstract: Background and Purpose-Several studies have shown, in different populations, that modest elevation of plasma C-reactive protein (CRP) in the range seen in apparently healthy individuals is a strong predictor of future vascular events. Elevated plasma CRP concentrations are also associated with an increased risk of cerebrovascular events and an increased risk of fatal and nonfatal cardiovascular events in ischemic stroke patients. These epidemiological and clinical observations suggest that determination of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
6
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(216 citation statements)
references
References 200 publications
8
197
6
5
Order By: Relevance
“…The role of CRP in predicting recurrent events in patients with cerebrovascular disease is controversial. 18 In a cohort of 467 patients with ischemic stroke from the Northern Manhattan Stroke Study, CRP was not associated with recurrent stroke or the composite of stroke, MI, and vascular death, but was associated with mortality. 11 In several smaller cohorts of patients with acute ischemic stroke, CRP has been predictive of recurrent vascular events or death, but with variable results depending on the timing of CRP measurement.…”
Section: Discussionmentioning
confidence: 98%
“…The role of CRP in predicting recurrent events in patients with cerebrovascular disease is controversial. 18 In a cohort of 467 patients with ischemic stroke from the Northern Manhattan Stroke Study, CRP was not associated with recurrent stroke or the composite of stroke, MI, and vascular death, but was associated with mortality. 11 In several smaller cohorts of patients with acute ischemic stroke, CRP has been predictive of recurrent vascular events or death, but with variable results depending on the timing of CRP measurement.…”
Section: Discussionmentioning
confidence: 98%
“…Myelination of CNS>PNS Diagnosis [104] Infarct volume [103] Stroke severity [103] Inflammatory Biomarkers CRP Liver synthesis Acute phase reactant, role in atherotherombosis & ischemic injury [105] Diagnosis [106] Stroke risk [62,[107][108][109] IL-6 Cytokine from T-cells+ macrophages Acute phase response, fever Infarct volume [53][54][55]110] Stroke Severity [110] END [53,54] TNF-α Cytokine, inflammatory cells Inflammation, Acute phase response Infarct volume [53] Stroke Severity [53] END [72] VCAM 1 Immunoglobulin Leukocyte-endothelial cell interaction Diagnosis [19] Infarct volume [53] ICAM 1 Immunoglobulin Leukocyte-endothelial cell interaction…”
Section: Protein Biomarkers In Ischemic Strokementioning
confidence: 99%
“…Several prospective studies have been indicated that brain injury secondary to a sICH is characterized by acute local inflammation deterioration in sICH [11,12]. Another of the most promising of these inflammatory markers is C-reactive protein (CRP), a biomarker of inflammation that has been shown to predict prognosis in ischemic stroke after adjustment for all major prognostic components [15]. Unfortunately, previous studies have only marginally evaluated CRP as a prognostic marker after sICH with contrasting results [14,16] .This has led to a renewed interest in the study of inflammation markers, including CRP and WBC count, in sICH.…”
Section: Introductionmentioning
confidence: 99%